Para-aortic lymphadenectomy in endometrial cancer patients with left-sided inferior vena cava: A case report and literature review - Yuriko Higashi; Shinichi Togami; Hiroaki Kobayashi (Elsevier, 2024)
Objective: The incidence of left-sided inferior vena cava (IVC) is extremely low. However, without a preoperative diagnosis of left-sided IVC, the risk of intraoperative vascular injury during para-aortic lymph node (PAN) lymphadenectomy is high. Case report: Herein, we present two cases in which left-sided IVCs were diagnosed using preoperative imaging. PAN lymphadenectomies were safely performed in these patients with endometrial cancer. In the first case, the left-sided IVC crossed the abdominal aorta after the left renal and gonadal veins had drained into it and joined the right renal vein. In the second case, the left-sided IVC crossed the abdominal aorta after the left renal and gonadal veins flowed into it and the ascending lumbar vein flowed into the right side. Conclusion: These cases demonstrate that even in the presence of vascular malformations, PAN lymphadenectomy can be performed safely by employing preoperative anatomical imaging analysis and judicious intraoperative surgical maneuvers to avoid vascular injury.